Pengembangan Organizational Citizenship Behavior Dan Budaya Organisasi Terhadap Kinerja Pegawai Melalui Motivasi Pada Badan Keuangan Kabupaten Ngawi - Ifah Lathifah; Hadi Prayitno (ProBank, 2026)
The purpose of this study is to empirically analyze the role of organizational citizenship behavior development and organizational culture on motivation that impacts employee performance at the Ngawi Regency Financial Agency. The analysis technique used is by using instrument tests that include validity and reliability tests, linearity tests, regression analysis, path analysis, t-test, F-test, coefficient of determination test and correlation analysis. The results of the study are Organizational Citizenship Behavior has a positive and insignificant effect on motivation. Organizational culture has a positive and significant effect on motivation. Organizational Citizenship Behavior has a positive and insignificant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. The results of the calculation of the total R2 value of 0.882 can be interpreted that variations in employee performance at the Ngawi Regency Financial Agency are explained by the variables of Organizational Citizenship Behavior, organizational culture and motivation by 88.2% and the remaining 11.8% is explained by other variables outside the research model such as training and work climate. The conclusion of the path analysis is that the direct influence of Organizational Citizenship Behavior and organizational culture on performance produces a greater value than the indirect path. So it is more effective with a direct path in improving performance.